Inclusive Growth Analysis in Economies Prone to International Migration - Keller, Jennifer (World Bank, Washington, DC, 2017)
Inclusive growth (IG) analysis involves analyzing the available data in a country to determine the best course of action for accelerating growth and or improving the distribution of the opportunities and benefits from the growth process. In economies in which international migration is a significant trend, that determination may be especially challenging. The international migration phenomenon can contribute to (or detract from) growth and its distribution through myriad number of complex and sometimes divergent channels, and these effects can change substantially over time. The ability to analyze these impacts, however, is often significantly handicapped by a lack of appropriate data. Moreover, because the migration decision is inherently a private decision made by households in the best interest of their welfare, determining the policy conclusions based on the results of inclusive growth analysis is often unclear. Governments are rightfully wary of interfering with the migration process. This paper examines the issue of international migration in inclusive growth. The aim is to provide the practitioners of inclusive growth diagnostics a useful framework for assessing the nature of the international migration phenomenon, and to highlight the key tools utilized in evaluating its current and potential impact on shared growth.